2022
DOI: 10.1097/pcc.0000000000003071
|View full text |Cite
|
Sign up to set email alerts
|

Novel Identification of Myeloid-Derived Suppressor Cells in Children With Septic Shock

Abstract: Immunoparalysis in children with septic shock is associated with increased risk of nosocomial infections and death. Myeloid-derived suppressor cells (MDSCs) potently suppress T cell function and may perpetuate immunoparalysis. Our goal was to test the hypothesis that children with septic shock would demonstrate increased proportions of MDSCs and impaired immune function compared with healthy controls.DESIGN: Prospective observational study. SETTING: Fifty-four bed PICU in a quaternary-care children's hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A ventricle is in the plateau phase of the Frank-Starling curve, and even increasing cardiac preload with fluids does not noticeably increase cardiac output. Previous study has found that patients with volume responsiveness account for only 40-50% of hemodynamically unstable patients 26 . As a result, excessive fluid replacement can cause pulmonary oedema and heart failure, affecting the metabolism and oxygenation of organs and tissues, aggravating the patient's condition and ultimately leading to increased mortality 27 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A ventricle is in the plateau phase of the Frank-Starling curve, and even increasing cardiac preload with fluids does not noticeably increase cardiac output. Previous study has found that patients with volume responsiveness account for only 40-50% of hemodynamically unstable patients 26 . As a result, excessive fluid replacement can cause pulmonary oedema and heart failure, affecting the metabolism and oxygenation of organs and tissues, aggravating the patient's condition and ultimately leading to increased mortality 27 .…”
Section: Discussionmentioning
confidence: 95%
“…More attention should be paid to the cardiac function to evaluate the volume responsiveness. If both the left and right ventricles are in the ascending phase of the Frank-Starling curve, there is volume responsiveness as OC will increase with increased cardiac preload after fluid resuscitation 25 . A ventricle is in the plateau phase of the Frank-Starling curve, and even increasing cardiac preload with fluids does not noticeably increase cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…, opting for 500 pg/ml LPS from Salmonella abortus equi, as opposed to their 2.5 ng/ml. This decision was informed by prior studies from Hall and colleagues [ 28 33 ]. Our results suggest a consistent link between LPS-induced TNF production and patient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…AFP with glucocorticoids or indomethacin stimulate MDSCs' activity. That establishes MDSC as a potential therapeutic target for immune suppression during ADs, transplantation, trauma, septic shock 73 , and other conditions.…”
Section: Recombinant Afp As a Drugmentioning
confidence: 98%